1992
DOI: 10.1093/oxfordjournals.aje.a116549
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Two General Job-Exposure Matrices in a Study of Lung Cancer Morbidity in the Zutphen Cohort

Abstract: Data from a general population cohort of 878 men from the town of Zutphen, The Netherlands, were used to evaluate the performance of two general job-exposure matrices. Exposures generated by the job-exposure matrices on the basis of job histories were compared. The validity of those exposures was measured against exposures reported by the participants in 1977/1978. The performance of the different exposure measures was assessed in proportional hazards analyses of lung cancer morbidity incidence. The two genera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
46
1

Year Published

2003
2003
2014
2014

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 62 publications
(50 citation statements)
references
References 0 publications
3
46
1
Order By: Relevance
“…It could be that the validity of the self-reported exposure to various agents is higher for women than men (18). However, the JEM-based exposure characterization is less subject to recall bias than the self-reported exposure characterization (6,19,20). Thus, a tendency for a stronger relationship between airborne occupational exposures and asthma, and symptoms in women could be due to women being more vulnerable to airborne pollutants than men (21,22).…”
Section: Skorge Et Almentioning
confidence: 99%
See 2 more Smart Citations
“…It could be that the validity of the self-reported exposure to various agents is higher for women than men (18). However, the JEM-based exposure characterization is less subject to recall bias than the self-reported exposure characterization (6,19,20). Thus, a tendency for a stronger relationship between airborne occupational exposures and asthma, and symptoms in women could be due to women being more vulnerable to airborne pollutants than men (21,22).…”
Section: Skorge Et Almentioning
confidence: 99%
“…Several studies have compared self-reported and JEM-based exposure characterization, and found them to be equal (24) or the JEM more precise (19,20). However, it has been argued that the JEM should be adjusted to the geographical area, the time period, and the disease under study (6,7). The weaker association found when using a JEM compared with a self-reported exposure characterization in this population could be due to the applied JEM not being specific to the study population even though it was designed for airway disease.…”
Section: Skorge Et Almentioning
confidence: 99%
See 1 more Smart Citation
“…In the approach presented in our paper, expert judgment steps allowed the possibility to revise the specific exposures generated by the JEM on the basis of job description. This resulted in different exposure classifications within subjects with the same job code, and probably increased specificity, which is favorable in this type of community-based studies (Kromhout et al, 1992). Although the labor-intensive expert judgment steps in our study resulted in relevant modifications, substantial changes were only made in a few categories.…”
mentioning
confidence: 95%
“…The method used in the current study could potentially lead to an underreporting of exposure. When selfreport and expert assessment are compared, the specificity of the self-assessment of exposure is high (approximately 0.90), but the sensitivity is lower (less than 0.24 to 0.85) (33)(34)(35)(36). In a recent study, 53% of men indicated exposure to dusts, gases, or fumes based on self-report whereas 74% were classified as exposed after expert assessment (24).…”
Section: Discussionmentioning
confidence: 99%